“Protección del desarrollo de productos elaborados en la carrera de Agroindustria a través del secreto industrial de la cerveza artesanal de Quinua (Chenopodium quinoa)”. - Rojas Guachi, Ivette Gabriela (2022)
The Ecuadorian Higher Education National System Institutions are called to produce proposals and approaches to seek the problems solution, what afflict our nation; the inclusión these proposals will produce a fairer ,more equitable and supportive society, such is the Agroindustrial Engineering career case, which seeks to contribute to the country agroindustrial sector, transferring the knowledge and skills developed within the university campuses, through the execution this project for the products industrial property registration,wich are developed within the Agroindustrial Engineering career. Therefore, in compliance with the Higher Education Quality Assurance Council requirements and contemplated in the Strategic Plan for Institutional Development (PEDI) force since 2021, the quinoa craft beer (Chenopodium quinoa), through registration in the Intellectual Rights National Service SENADI at the appointment from Cotopaxi Technical University. This quinoa craft beer industrial secret registration diligence,it was performed by collecting information from developed one research projects in 2016 within the Agroindustrial Engineering career,whose information lies in the repository from Cotopaxi Technical University later,it carries said documentation,what consists title,methodology ,flow diagram,formulation,material balance;to procolize and notarize with the external legal advisor help, at the end,it is registered in the regular national entity,being the academy,the legal rights absolute beneficiary of same purposes that require it.